HUBUNGAN KELELAHAN POSTPARTUM DENGAN MOTIVASI PEMBERIAN ASI - Riski Oktafia; Revita Deviana (STIKes MERCUBAKTIJAYA, 2021)
THE WOMEN'S CONDITION AFTER CHILDBIRTH UNDERGOES PHYSICAL AND PSYCHOLOGICAL CHANGES. CHANGES AFTER CHILDBIRTH CAUSE FATIGUE IN THE POSTPARTUM PERIOD. POSTPARTUM FATIGUE MAKES THE MOTIVATION OF BREASTFEEDING DECREASE. THIS STUDY AIMS TO FIND OUT THE RELATIONSHIP OF FATIGUE WITH MOTIVATION FOR BREASTFEEDING IN THE POSTPARTUM PERIOD. THE DESIGN OF THIS STUDY WAS A QUANTITATIVELY ANALYTICAL CORRELATION WITH A CROSSECTIONAL APPROACH PERFORMED ON 95 POSTPARTUM MOTHERS WITH PURPOSIVE SAMPLING TECHNIQUES. THE QUESTIONNAIRES USED ARE THE POSTPARTUM FATIGUE SCALE (PFS) AND BREASTFEEDING MOTIVATIONAL INSTRUCTIONAL MEASUREMENT SCALE (BMIMS). STATISTICAL ANALYSIS USES THE SPEARMAN RHO TEST WITH SIGNIFICANCE P<0.05. THE RESULTS OF THIS STUDY SHOWED THAT POSTPARTUM MOTHERS WHO EXPERIENCED HIGH LEVELS OF FATIGUE AS MUCH AS 91 (95.8%), MODERATE AS MUCH AS 2 (2.1%), LOW AS MANY AS 2 (2.1%) RESPONDENTS. THE MOTIVATION LEVEL OF BREASTFEEDING WAS LOW BY 50 (52.6%), AND THE MOTIVATION OF BREASTFEEDING WAS LOW AS MUCH AS 40 (47.4%) RESPONDENTS. THE CONCLUSION OF THIS STUDY THERE IS A SIGNIFICANT ASSOCIATION BETWEEN FATIGUE AND MOTIVATION OF BREASTFEEDING IN POSTPARTUM (P = 0.001). HEALTH SERVICE ARE EXPECTED TO IMPROVE THE QUALITY OF SERVICE IN THE POSTPARTUM PERIOD BY ASSESSING POSTPARTUM FATIGUE EARLY TO INCREASE MATERNAL MOTIVATION IN BREASTFEEDING.